Case Report: Laparoscopy-assisted resection for intra-abdominal gossypiboma masquerading as a jejunal tumor (with video) - Han, Yihui; Yang, Wenming; Dai, Wenshu; Ma, Qin; Yuan, Tao; Yang, Yun; Lu, Yanrong; Zhang, Bo; Zhang, Mingming (Frontiers in Oncology, 2023)
Introduction: Intra-abdominal gossypiboma, a cotton-based retained foreign body after an abdominal surgery, is associated with various clinical manifestations and complications. Its infrequent occurrence and unpredictability make its early diagnosis particularly challenging. We herein present an atypical case of intra-abdominal gossypiboma mistaken for a jejunal tumor. Case presentation: A 33-year-old female presented to the emergency room with an acute episode of progressive abdominal pain and distention, nausea, and vomiting for 20 hours. She had undergone an urgent cesarean section due to fetal tachycardia seven years prior. The initial diagnosis of small bowel obstruction (SBO) due to a jejunal tumor was established by computed tomography. Subsequent to successful medical management of the SBO, a laparoscopy-assisted resection of the mass and the adherent jejunal segment was conducted, culminating in a primary side-to-side jejunojejunostomy. Examination of the excised tissue revealed an approximately spherical fibrous mass, 6 × 6 × 5 cm in dimension, embedded in the jejunal wall, housing a 20 × 20-cm gauze. Postoperative recovery and routine follow-up ensued without complications. Conclusion: In light of this case, the need for clinicians to maintain an elevated awareness and suspicion of gossypiboma should be accentuated when evaluating an intra-abdominal mass, especially in patients with a prior history of high-risk laparotomy. Laparoscopic surgery stands out as a technically proficient and minimally invasive strategy for diagnosing and treating intra-abdominal gossypiboma. Besides, it is imperative to emphasize the importance of meticulous surgical procedures and postoperative protocols to prevent such oversights, reaffirming the need for consistent intraoperative counts and checks of surgical items.